FAKTOR PENDORONG DAN PENGHAMBAT IMPLEMENTASI KEGIATAN PROGRAM TNI MANUNGGAL MEMBANGUN DESA (TMMD) DI KOTA SEMARANG - Lwihpakerti, Madva; Purnaweni, Hartuti (Journal of Public Policy and Management Review, 2018)
One of the TNI's bhakti operations that directly touched the community's life needs was the TNI Manunggal Membangun Desa (TMMD), by involving the local government as a work partner. The TNI Manunggal Membangunan Desa (TMMD) program took part in helping the Semarang City Government to help the community to be empowered, thereby improving the welfare of the community through physical and non-physical development. In this study using the theory of Edwards III to consider four factors in implementing public policy: Communication, Resources, Acting Attitudes, Bureaucratic Structure. Factors that are considered as supporting factors in the implementation of the TNI Manunggal Bangunan Desa (TMMD) program activities in Semarang City are the implementing communication and disposition. The factor that is considered as an inhibiting factor in the implementation of the TNI Manunggal Pembangunan Desa (TMMD) program activities in Semarang City is the resources and bureaucratic structure. The need to increase the quantity of human resources. The creation of a special SOP on the TMMD program so that operational implementation has a clear position base